Global Insights on Public Perceptions and Engagement based on TikTok politics - Devi, Indah Kartika; Sinduwiatmo, Kukuh (Indonesian Journal of Public Policy Review, 2024)
In the digital era, social media platforms like TikTok are increasingly used for political campaigns. This study examines the PAN party's use of the viral TikTok song "PAN 12" to engage students, using Davidoff’s public perception theory. Employing a qualitative descriptive method with six student informants from Sidoarjo, the research reveals mixed perceptions: some find the content engaging, while others criticize it for lacking substantive political content. The findings highlight that while TikTok can reach a wider audience and enable direct interaction with voters, it risks prioritizing popularity over political substance. Therefore, the PAN party should address criticisms with transparency and substantial communication to enhance understanding of their political goals. Highlights: TikTok engages a wider audience for political campaigns. "PAN 12" song evokes mixed reactions from students. Balance popularity with substantive communication to address criticisms. Keywords: Social Media, TikTok, Political Campaigns, Public Perception, Student Engagement